Human anatomy & physiology : - Martin, Terry R. (McGraw-Hill Higher Education, 2007)
This lab manual offers excellent, full color dissection photos of the fetal pig with matching, corresponding labeled art. Web site activities found in numerous labs give students additional resources for learning.